New and rare Aloninae (Cladocera: Anomopoda: Chydoridae) from Indochina - Sinev, Artem Y.; Kotov, Alexey A. (Zootaxa, 2012)
Several poorly known cladocerans of the subfamily Aloninae (Cladocera: Anomopoda: Chydoridae) from Indochina re-gion are reinvestigated. Revision of the genus Anthalona Van Damme, Sinev & Dumont 2011 from Thailand, Cambodiaand Vietnam reveals that the region is inhabited by Paleotropic Alona harti harti Van Damme, Sinev & Dumont, 2011 anda new species, Alona sanoamuangae sp. nov., which appears to be an Indochinese endemic. It has a number of featuresprimitive for the genus, including non-specialised IDL setae and non-differentiated scraping setae. So far, these characterswere recorded only in the Congolese A. simplex Van Damme, Sinev & Dumont, 2011, but A. sanoamuangae sp. nov. dif-fers from it in the trilobed cosmaria of the lateral head pores. An updated key for the Anthalona of Eurasia and Africa isprovided. The endemic Alona freyi Idris & Fernando, 1981 belongs to the recently described genus Matralona VanDamme & Dumont, 2010, sharing numerous common features with the type species, Matralona simoneae (Dumont,1981). Alona macronyx Daday, 1898, despite numerous unique features, should be moved from Alona to Celsinotum Frey,1999, and the diagnosis of Celsinotum should be emended. Finally, a new taxon with several unique features, Coronatellasp., was found in Thailand. Our investigation demonstrates once more the necessity of successive revisions of cladoceran taxa, even in relatively well-studied regions.